The Impact Of High-Performance Human Resource Practices On Intrapreneurial Behaviour In The Oil And Gas Sector In Iraq - Haroon Ahmed Matloob; Karuppan, Valliappan Raju; Al-Shami, Samer Ali Hussein (The Mattingley Publishing Co., Inc., 2020)
This paper aims to provide a clarification of the relationship between high performance, human resource practices and Intrapreneurial Behavior. This paper also attempts to illustrate the role of affective commitment as a mediator in the relationship. The sample used in this study included nine organization in Iraq‘s oil and gas industry. The paper argues that previous studies focus on the positive impact of human resource management practices.Contrary to previous research, this paper shows the positive relation between high performance human resource practice and intrapreneurial behavior and how affective commitments mediate the relationship. The study findings showed that human resource practices influence the attitudes and behaviour of people within organizations. Besides, the study suggests that high-performance human resource practice can operate through a path that connects affective commitments and intrapreneurial behavior.